The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1002/jsfa.2740300608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of domestic preparation of cereals and legumes on ionisable iron

Abstract: Effect of simple domestic processing on ionisable iron from cereals and legumes was investigated using an in vitro method. Two-fold increase was observed when legumes and cereal were germinated for different periods. In the case of legumes, increase was observed only with the whole grain, whereas no such changes were observed with decorticated legume. The ionisable iron from bread was higher (nearly twice) when compared with that from chapathi, prepared from the same wheat. The total iron was higher in the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Increases in iron ionizability could be observed during germination of green gram or wheat as early as 24 h, whereas such an effect was seen only after extended periods (48 and 72 h) in the case of chickpea. In the case of legumes, an increase was observed only with the whole grain, whereas no such changes were observed with decorticated legumes (Prabhavathi and Rao, 1979). In our study, improved iron bioacessibility was observed in chickpea germinated even for 24 h. Thus, our observations on the improved bioaccessibility of iron upon germination of grains are in concurrence with several such observations reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increases in iron ionizability could be observed during germination of green gram or wheat as early as 24 h, whereas such an effect was seen only after extended periods (48 and 72 h) in the case of chickpea. In the case of legumes, an increase was observed only with the whole grain, whereas no such changes were observed with decorticated legumes (Prabhavathi and Rao, 1979). In our study, improved iron bioacessibility was observed in chickpea germinated even for 24 h. Thus, our observations on the improved bioaccessibility of iron upon germination of grains are in concurrence with several such observations reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…A two-fold increase in in vitro iron absorption has been observed in legumes and cereals germinated for different periods (Prabhavathi and Rao, 1979). Increases in iron ionizability could be observed during germination of green gram or wheat as early as 24 h, whereas such an effect was seen only after extended periods (48 and 72 h) in the case of chickpea.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some of these processing methods are fermentation, frying and cooking (Raghuuath and Belavady, 1997;Prablivathi and Narasinga, 1979). These processing also introduce chemicals that affect nutritional values adversely.…”
Section: Introductionmentioning
confidence: 99%
“…Sprouted legumes are rich sources of B-group vitamins and are also known to contain some provitamin A and vitamin E (Pomeranz and Robbins, 1971;Voss and Piendl, 1978). An increase in the ionizable iron from 4.1 to 7.7% and insoluble iron from 10.4 to 16.4% on germination of cereals has been reported by Prabhavathi and Rao (1979). Similarly, increases in acid extractability of calcium, phosphorus, iron, zinc, and copper from 48 to 69%, 36 to 48%, 36 to 50%, 42 to 50%, and 35 to 57%, respectively, were observed in malted wheat, malted green gram, and jaggery-based weaning foods (Gahlawat and Sehgal, 1993).…”
Section: Vitamins and Mineralsmentioning
confidence: 85%